Eco-physiology of maize crops under combined stresses - Cagnola, Juan I. (2023)
The yield of maize (Zea mays L.) crops depends on their ability to intercept sunlight throughout the growing cycle, transform this energy into biomass and allocate it to the kernels. Abiotic stresses affect these eco-physiological determinants, reducing crop grain yield below the potential of each environment. Here we analyse the impact of combined abiotic stresses, such as water restriction and nitrogen deficiency or water restriction and elevated temperatures. Crop yield depends on the product of kernel yield per plant and the number of plants per unit soil area, but increasing plant population density imposes a crowding stress that reduces yield per plant, even within the range that maximises crop yield per unit soil area. Therefore, we also analyse the impact of abiotic stresses under different plant densities. We show that the magnitude of the detrimental effects of two combined stresses on field-grown plants can be lower, similar or higher than the sum of the individual stresses. These patterns depend on the timing and intensity of each one of the combined stresses and on the effects of one of the stresses on the status of the resource whose limitation causes the other. The analysis of the eco-physiological determinants of crop yield is useful to guide and prioritise the rapidly progressing studies aimed at understanding the molecular mechanisms underlying plant responses to combined stresses.